2017
DOI: 10.1002/hon.2454
|View full text |Cite
|
Sign up to set email alerts
|

A pilot phase II study of ofatumumab monotherapy for extranodal marginal zone B‐cell lymphoma of the mucosa‐associated lymphoid tissue (MALT) lymphoma

Abstract: These are the final results of the Ofatumumab in MALT lymphoma study (O‐MA 1), a pilot phase II trial evaluating the capacity and safety of ofatumumab to induce objective responses in patients with Helicobacter pylori eradication refractory or extragastric MALT lymphoma. Ofatumumab was given at 4 weekly doses (1000 mg) followed by 4 doses at 2‐month intervals starting at week 8. According to protocol, a total of 16 patients were recruited (median age 69 years; range 38‐85). Thirty one percent (5/16) of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The presence of plasmacytic differentiation might be of interest in this context, as plasma‐cells are CD20‐negative; an increase of plasmacytic differentiation following application of R has been reported in patients with MALT lymphoma 54 . Furthermore, the second generation compound ofatumumab, and also the CD20‐based radio‐immunotherapy with 90Y‐ibritumomab‐tiuxetan have been tested and found active in this context 47,49 . Ofatumumab was evaluated in a pilot trial of 16 patients (31% gastric patients, 69% extragastric patients) resulting in an ORR of 81% and 50% CRs, and while larger series and long‐term data are missing, this appears to be at least as effective as R‐monotherapy based on these pivotal data 47 .…”
Section: Molecular Targeted Treatment For Malt Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of plasmacytic differentiation might be of interest in this context, as plasma‐cells are CD20‐negative; an increase of plasmacytic differentiation following application of R has been reported in patients with MALT lymphoma 54 . Furthermore, the second generation compound ofatumumab, and also the CD20‐based radio‐immunotherapy with 90Y‐ibritumomab‐tiuxetan have been tested and found active in this context 47,49 . Ofatumumab was evaluated in a pilot trial of 16 patients (31% gastric patients, 69% extragastric patients) resulting in an ORR of 81% and 50% CRs, and while larger series and long‐term data are missing, this appears to be at least as effective as R‐monotherapy based on these pivotal data 47 .…”
Section: Molecular Targeted Treatment For Malt Lymphomamentioning
confidence: 99%
“…Furthermore, the second generation compound ofatumumab, and also the CD20‐based radio‐immunotherapy with 90Y‐ibritumomab‐tiuxetan have been tested and found active in this context 47,49 . Ofatumumab was evaluated in a pilot trial of 16 patients (31% gastric patients, 69% extragastric patients) resulting in an ORR of 81% and 50% CRs, and while larger series and long‐term data are missing, this appears to be at least as effective as R‐monotherapy based on these pivotal data 47 . Radio‐immunotherapy with 90Y‐ibritumomab‐tiuxetan, was in addition to preliminary retrospective data, investigated in a phase II study including a total of 30 patients (43% gastric, 57% extragastric) 49 .…”
Section: Molecular Targeted Treatment For Malt Lymphomamentioning
confidence: 99%
“… 10 In the O-MA1 trial, ofatumumab showed an ORR of 81% with a CR rate of 50% in 16 patients with MALT lymphoma. 11 Those next generation compounds might be of interest for further studies to potentially overcome resistance to R-monotherapy and also for combination regimens.…”
Section: Systemic Treatment Of Malt Lymphomamentioning
confidence: 99%
“…Hence, the decision of radiation versus chemotherapy can be made based on individual patient's profile and the center's experience [ 19 ]. In advanced stage disease when systemic treatment is needed, chemotherapy and/or immunotherapy with anti-CD20 monoclonal antibodies can be considered [ 19 , 20 ]. Surgical resection is recommended when a colorectal MALT lymphoma does not respond to eradication therapy or chemotherapy, provided it is localized without dissemination [ 21 ].…”
Section: Discussionmentioning
confidence: 99%